The danger of desire ebook - Jeffries, Sabrina (Sinful Suitors, 2016)
The third book in the sexy Sinful Suitors Regency romance series, this heart-pounding story shows why New York Times bestselling author Sabrina Jeffries is one of the most beloved historical romance writers today. To root out the card cheat responsible for her brother's death, Miss Delia Trevor spends her evenings dancing her way through high society balls, and her late nights disguised as a young man gambling her way through London's gaming hells. Then one night, handsome Warren Corry, the Marquess of Knightford, a notorious member of St. George's Club, recognizes her. When he threatens to reveal her secret, she's determined to keep him from ruining her plans, even if it means playing a cat-and-mouse game with the enigmatic rakehell. Warren knows the danger of her game, and he refuses to watch her lose everything while gaining justice for her late brother. But when she starts to delve beneath his carefully crafted façade, can he keep her at arm's length while still protecting her? Or will their hot desires explode into a love that transcends the secrets of their pasts?